6x (3x+5) – 2x (3x-2) + (17-x) (x-1) + x (x-18) =0

Question

6x (3x+5) – 2x (3x-2) + (17-x) (x-1) + x (x-18) =0

in progress 0
Jade 4 tuần 2021-08-25T07:23:57+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-25T07:25:11+00:00

    Đáp án:

     xin hay nhất nha bạn

    Giải thích các bước giải:

     

    0
    2021-08-25T07:25:12+00:00

    Bạn tham khảo: 

    $6x (3x+5) – 2x (3x-2) + (17-x) (x-1) + x (x-18) =0$

    $=18x^2 + 30x – 6x^2 – 4x + 17x + 17 + x^2 + x – x^2 – 18x = 0$

    $= 18x^2 + 30x + 17x – 4x – 18x+ x^2 – x^2 + x =0$

    $ =18x^2 + 25 + 0 + x = 0$

    $=18x^2 + x + 25 = 0$

    $= 18x^2 + x = -25$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )